ChemInform Abstract: Microwave‐Assisted Telescoped Cross Metathesis‐Ring Closing Aza‐Michael Reaction Sequence: Step‐Economical Access to Nicotine—Lobeline Hybrid Analogues. Issue 13 (March 2016) - Drege, E.; Oko, J.; Venot, P.‐E.; Gigant, N.; Joseph, D.
Abstract: The sequence for the access to nicotine‐natural nicotinic acetylcholine receptor ligand hybrids includes a cross‐metathesis and a ring‐closing step.